The Anti-mycobacterial Activity of a Diterpenoid-Like Molecule Operates Through Nitrogen and Amino Acid Starvation - Crusco, Alessandra; Baptista, Rafael; Bhowmick, Sumana; Beckmann, Manfred; Mur, Luis A. J.; Westwell, Andrew D.; Hoffmann, Karl F. (Frontiers in Microbiology, 2019)
A library of 14 minimally cytotoxic diterpenoid-like compounds (CC50 > 70 μM on HepG2 human liver cells) was screened against Mycobacterium smegmatis, Staphylococcus aureus, and Escherichia coli to determine antimicrobial activity. Some compounds with a phenethyl alcohol (PE) core substituted with a β-cyclocitral derivative demonstrated anti-mycobacterial activity, with the most active being compound 1 (MIC = 23.4 mg/L, IC50 = 0.6 mg/L). Lower activity was exhibited against S. aureus, while no activity was displayed against E. coli. Low cytotoxicity was re-confirmed on HepG2 cells and additionally on RAW 264.7 murine macrophages (SI for both cell lines > 38). The sub-lethal (IC50 at 6 h) effect of compound 1 on M. smegmatis was examined through untargeted metabolomics and compared to untreated bacteria and bacteria treated with sub-lethal (IC50 at 6 h) concentrations of the antituberculosis drugs ethambutol, isoniazid, kanamycin, and streptomycin. The study revealed that compound 1 acts differently from the reference antibiotics and that it significantly affects amino acid, nitrogen, nucleotides and folate-dependent one-carbon metabolism of M. smegmatis, giving some insights about the mode of action of this molecule. A future medicinal chemistry optimization of this new anti-mycobacterial core could lead to more potent molecules.